“Middle Ground,” “Duality,” and “Diversimilarity” as Responses to Postcolonial and Global Challenges in Chinua Achebe’s “The Education of a British-Protected Child” and “No Longer at Ease” - Culea, Mihaela (Respectus Philologicus, 2013)
This paper discusses two literary works by Chinua Achebe—No Longer at Ease (1960) and The Education of a British-Protected Child (2011)—in the context of the issue of diversity in the postcolonial setting. It aims to approach Achebe’s work from a new perspective, by applying a theoretical paradigm employed in business to the study of literature and culture. The “diversimilarity” paradigm, used for managing cultural diversity in organisations, is applied and shown to be pertinent to the investigation of literature, too. The methodology employed combines theoretical data with the practical implications of the conceptual framework on Achebe’s work. The paper starts with a discussion of the diversity concept and then moves on to tackle the diversimilarity paradigm in business. Then the investigation focuses on Achebe’s “duality” and “middle ground” concepts as they assist diversimilarity, concepts which work together at the levels of mentality, ideology, and identity. Finally, the paper focuses on language and the methods proposed by Achebe to manage and solve the existing linguistic diversity problems in Nigeria. The findings show that in the works explored, the diversimilarity paradigm is assisted by other concepts as solutions for the Nigerian people to cope with diversity. Moreover, Achebe shows that the other conceptions that support diversimilarity are still effective, even though they are rooted in the ancestral values of his Igbo people. The originality of the paper results from placing Achebe’s literary work in the context of contemporary concerns related to human identity in the postcolonial globalized environment and from expanding the scope and methods of literary research by employing concepts from other areas of human activity. Thus, the intersection between the worlds of the economy and culture seems fruitful for the investigation of cultural diversity.
Keywords: Chinua Achebe; Diversity; Similarity; Middle Ground; Duality; Diversimilarity; Language; Culture